Synthesis and Antibacterial Activity of Cobalt (III) and Nickel (II) Complexes - Ahmad, Parwa Rostam; Muhammad, Muhammad Tahir; Ahmed, Ako Yousif (International Journal of Psychosocial Rehabilitation, 2020)
Due to the ability of metal ion complexes to form octahedral and square planar molecular geometry they have very good potential to achieve unique type of antibacterial compounds. In order to evaluate the role of homoleptic monodentate ligand on its antibacterial properties, novel transition 3d metal complexes of nickel (II), cobalt (III) were synthesized as hexaamminecobalt (III) chloride and hexaamminenickel (II) chloride complexes by using cobalt chloride hexahydrate and nickel chloride hexahydrate for the purpose of investigating its antimicrobial activities. The antimicrobial potentials of these complexes were tested against gram positive human pathogenic bacteria Staphylococcus aureus by using paper disc diffusion method on the agar cup method. The biological activity studies indicated that cobalt (III) complex exhibited activity better than the nickel (II) complex. The complexes with high concentration on the nutrient agar showed very good anti-bacterial activity compare to low concertation complexes on the nutrient agar, in spite of, antibacterial activity on nutrient agar showed better result than blood agar.